Facilitating implementation of primary care mental health over time and across organizational contexts: a qualitative study of role and process - Mona J. Ritchie; Louise E. Parker; JoAnn E. Kirchner (BMC, 2023)
Abstract Background Healthcare organizations have increasingly utilized facilitation to improve implementation of evidence-based practices and programs (e.g., primary care mental health integration). Facilitation is both a role, related to the purpose of facilitation, and a process, i.e., how a facilitator operationalizes the role. Scholars continue to call for a better understanding of this implementation strategy. Although facilitation is described as dynamic, activities are often framed within the context of a staged process. We explored two understudied characteristics of implementation facilitation: 1) how facilitation activities change over time and in response to context, and 2) how facilitators operationalize their role when the purpose of facilitation is both task-focused (i.e., to support implementation) and holistic (i.e., to build capacity for future implementation efforts). Methods We conducted individual monthly debriefings over thirty months with facilitators who were supporting PCMHI implementation in two VA networks. We developed a list of facilitation activities based on a literature review and debriefing notes and conducted a content analysis of debriefing notes by coding what activities occurred and their intensity by quarter. We also coded whether facilitators were "doing" these activities for sites or "enabling" sites to perform them. Results Implementation facilitation activities did not occur according to a defined series of ordered steps but in response to specific organizational contexts through a non-linear and incremental process. Amount and types of activities varied between the networks. Concordant with facilitators' planned role, the focus of some facilitation activities was primarily on doing them for the sites and others on enabling sites to do for themselves; a number of activities did not fit into one category and varied across networks. Conclusions Findings indicate that facilitation is a dynamic and fluid process, with facilitation activities, as well as their timing and intensity, occurring in response to specific organizational contexts. Understanding this process can help those planning and applying implementation facilitation to make conscious choices about the facilitation role and the activities that facilitators can use to operationalize this role. Additionally, this work provides the foundation from which future studies can identify potential mechanisms of action through which facilitation activities enhance implementation uptake.